New and little-known heteroscleromorph Demospongiae from the continental shelf in the Amathole region (Eastern Cape, South Africa), with a note on the sponge biodiversity of the area - Payne, Robyn P.; Samaai, Toufiek; Janson, Liesl; Kerwath, Sven E.; Gibbons, Mark J. (Zootaxa, 2026)
The marine environment of the Amathole region, located in the central part of South Africa’s Eastern Cape Province near East London on the southeast coast, is characterized by a narrow continental shelf and strong currents. Due to these challenging sea conditions, the area remains relatively unexplored from a marine biodiversity perspective. Four hundred and fifty-seven specimens of heteroscleromorph demosponges were sampled using an epibenthic dredge from 48 sites at depths between 3–229 m in 2016. An additional 11 specimens were similarly collected in 2015, while a further six specimens from three additional sites were collected by SCUBA in 1999. Underwater visual surveys were undertaken onboard the R/V Phakisa using a Remotely Operated Vehicle during two expeditions in 2017, with in situ images used for species accounts. This study presents formal descriptions of 23 heteroscleromorph Demospongiae from the Amathole region, including several new records, with fifteen species new to South Africa. The dominant orders were Poecilosclerida and Tetractinellida, and the dominant families were Geodiidae, Isodictyidae, and Latrunculiidae. Although sponge assemblages changed with depth, and taxa-specific depth restrictions were observed, the peak in species richness in the mesophotic zone likely reflects collection effort. The fauna shows strong affinities with southern Africa, especially that of the Agulhas and southern Benguela ecoregions, as well as the Western Indian Ocean.